2004
DOI: 10.1063/1.1639132
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of charge transport to intrinsic strain in silicon oxynitride and Si-rich silicon nitride thin films

Abstract: Poole–Frenkel emission in Si-rich nitride and silicon oxynitride thin films is studied in conjunction with compositional aspects of their elastic properties. For Si-rich nitrides varying in composition from SiN1.33 to SiN0.54, the Poole–Frenkel trap depth (ΦB) decreases from 1.08 to 0.52 eV as the intrinsic film strain (εi) decreases from 0.0036 to −0.0016. For oxynitrides varying in composition from SiN1.33 to SiO1.49N0.35, ΦB increases from 1.08 to 1.53 eV as εi decreases from 0.0036 to 0.0006. In both mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
4
4
0
Order By: Relevance
“…It was reported that trap level in nitride films was drastically decreased with increasing the amount of excess silicon. 5) In our case, the energy levels of the traps of Si 3 N 4 and SRN (x ¼ 0:02) obtained from the temperature dependences of the P-F plots are 1.4 and 0.8 eV, respectively, which agree well with the reported values. Accordingly, the nitrogen concentration dependence of P-F current is mainly due to the change in the trap level.…”
Section: Resultssupporting
confidence: 90%
“…It was reported that trap level in nitride films was drastically decreased with increasing the amount of excess silicon. 5) In our case, the energy levels of the traps of Si 3 N 4 and SRN (x ¼ 0:02) obtained from the temperature dependences of the P-F plots are 1.4 and 0.8 eV, respectively, which agree well with the reported values. Accordingly, the nitrogen concentration dependence of P-F current is mainly due to the change in the trap level.…”
Section: Resultssupporting
confidence: 90%
“…From the slope of the best straight line fit through the data in Fig. 8(b) and (d), the conduction bulk trap depth can be calculated to be 1.02 and 1.18 eV, respectively for samples A and B, which are very close to values of some other reports [33,34,[38][39][40]. A Poole-Frenkel conduction bulk trap depth of 0.809 eV was reported in the as-grown stoichiometric SiN x by LPCVD at 780 8C [41].…”
Section: Methodssupporting
confidence: 85%
“…6 The barrier lowering energy at the point of breakdown ␤E BD 1/2 is independently determined from measurements of the breakdown field E BD and the optical dielectric constant ⑀ r , where ␤ = ͑q 3 / r 0 ͒ 1/2 . 7 It is noted that the current-voltage characteristics of samples investigated herein exhibit no cycling hysteresis associated with current stressing, implying that additional charge traps are not generated by the tests themselves.…”
mentioning
confidence: 74%